Discovery Learning to Improve Student Learning Outcomes for Class X Waste Material at SMK Negeri 1 Jombang - Wulandari, Anggun; Firdaus, Alfina Ni’matul; Santoso, Santoso (APPLICATION: Applied science in Learning Research, 2024)
Education is very important for developing the potential of human resources (HR) through high-quality teaching activities by maximizing discovery learning models that can be used as a bridge to encourage changes in teaching and learning activities more effectively because this learning requires students to be able to construct their knowledge with their experiences so that students can build their knowledge through discovery in learning experiences by interacting directly with objects and phenomena that exist around their environment. This study aims to determine the increase in student learning outcomes on waste material by applying the discovery learning model for class X SMKN 1 Jombang. The research method used was quasi-experimental research or quasi-experimental research with data collection techniques in the form of test instruments (pretest and posttest) which were tested using a paired sample t-test (t-test) using SPSS. The results showed that the paired sample t-test statistical test (t-test) showed that the sig (2-tailed) value was 0.005, so it could be concluded that there was a significant difference between learning outcomes in the pretest and post-test data in class X students of SMKN 1 Jombang. In general, the average pretest score for class X students was 82.193 and the score increased by 14.167 with a posttest score of 96.36. A high post-test score for students could indicate that the learning process was going well.